Authoring With Virtual Reality Nuggets—Lessons Learned - Horst, Robin; Naraghi-Taghi-Off, Ramtin; Rau, Linda; Doerner, Ralf (Frontiers in Virtual Reality, 2022)
Virtual Reality (VR) systems and VR content are complex, and their creation can mainly be conducted by experts in VR and related areas. That makes the use of VR challenging for experts from other domains, such as educators. In this paper, we build up on existing work and investigate the VR nugget concept – small self-contained VR systems that are built from educational design patterns. Particularly, we extend this concept and introduce structured authoring processes based on VR nuggets that show how standalone, combinable, and reusable VR software can serve as a meta-level guide for various VR applications and involve educators as domain experts. We conduct a user study with VR Forge, a VR-nugget-based authoring software tool, to draw conclusions on how pattern-based VR authoring tools should be designed to support domain experts. We compare our results with those of a related study of the VR nugget tool IN Tiles. Based on the comparative results of usability and hedonic quality measures, both anecdotal evidence and statistically significant results support the concept’s potential for VR authoring conducted by practitioners who are not experts in VR. We derive the recommendation that the design of a VR-nugget-based authoring environment will benefit from using both immersive and desktop user interface (UI) technologies and that the authoring workflow will need authors to frequently alternate between the technologies. We state findings and lessons learned from the development and the studies. We contribute insights in developing reusable and use-case-specific VR content and tools and propose authoring processes that focus on the tasks and goals of domain experts as the primary authoring role within educational VR development. Finally, the relevance of VR-nugget-based authoring is supported by anecdotal evidence gathered from over three years of investigating and applying it within three educational institutions and a company providing education services.